Metrics for Robot Proficiency Self-assessment and Communication of Proficiency in Human-robot Teams. - Norton, Adam.; Admoni, Henny.; Crandall, Jacob.; Fitzgerald, Tesca.; Gautam, Alvika.; Goodrich, Michael.; Saretsky, Amy.; Scheutz, Matthias.; Simmons, Reid.; Steinfeld, Aaron.; Yanco, Holly. (Tufts University. Tisch Library., 2023)
Keywords: Human-robot interaction, proficiency self-assessment, metrics, performance evaluation.; Topic: Computer systems organization / Robotic autonomy; Topic: General and reference / Metrics; Topic: General and reference / Evaluation; Topic: Human-centered computing / HCI design and evaluation methods; ACM Open.